PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP LIKUIDITAS PASAR SAHAM: STUDI PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG TELAH GO PUBLIC DI BURSA EFEK INDONESIA - Purba, Saut; Silalahi, Donalson (UNIKA Santo Thomas, 2021)
The purpose of this study is to obtain the empirical evidence about the impact of institutional ownership on stock market liquidity in manufacturing companies that have gone public on the Indonesia Stock Exchange. To achieve this goal, research was carried out on the Indonesia Stock Exchange using a research sample of 100 companies included in the manufacturing industry group. In explaining the effect of institutional ownership on stock market liquidity, 2 (two) models are used. The first model only uses institutional ownership as an independent variable, and the second model includes control variables, namely the standard deviation of price and volume of stock trading using the t test and the F test with Î± (alpha) of 10 percent. Based on the results of research and discussion, several conclusions can be drawn as follows: First, institutional ownership has a negative and significant effect on stock market liquidity and institutional ownership capacity in explaining stock market liquidity of 4.7 percent. Second, institutional ownership has a negative and significant effect on stock market liquidity, standard deviation of stock prices has a negative and significant effect on stock market liquidity, stock trading volume has a moderate and negative effect on stock market liquidity. The ability of these three variables in explaining stock market liquidity is 13.1 percent.Third, institutional ownership can increase stock market liquidity as indicated by the value of the direction coefficient and the level of significance of the variable of institutional ownership and the coefficient of direction and significance level of the standard deviation variable of stock prices.